22G Acquire vs. 20G Procore needle for endoscopic ultrasound-guided biopsy of pancreatic masses: a randomized study comparing histologic sample quantity and diagnostic accuracy - Karsenti, David; Palazzo, Laurent; Perrot, Bastien; Zago, Jacqueline; Lemaistre, Anne-Isabelle; Cros, Jérôme; Napoléon, Bertrand (Endoscopy, 2020)
Background Endoscopic ultrasound-guided fine-needle biopsy (EUS-FNB) has been suggested for obtaining high quality tissue samples from pancreatic tumors. We performed a multicenter randomized crossover trial comparing EUS-FNB with a 20G Procore needle vs. a 22G Acquire needle. The aims were to compare the quantity of targeted tissue (pancreas) and diagnostic accuracy for the two needles.Methods 60 patients admitted for EUS-FNB in three endoscopy units were included. One pass was performed consecutively with each needle, in a randomized order. Histologic material was studied in a blinded manner with respect to the needle. The primary end point was mean cumulative length of tissue core biopsies per needle pass.Results Final diagnosis was adenocarcinoma (n = 46; 77 %), neuroendocrine neoplasm (n = 11; 18 %), autoimmune pancreatitis (n = 2), and mass-forming chronic pancreatitis (n = 1). The mean cumulative length of tissue core biopsies per needle pass was significantly higher with the 22G Acquire needle at 11.4 mm (95 % confidence interval [CI] 9.0 – 13.8] vs. 5.4 mm (95 %CI 3.8 – 7.0) for the 20G Procore needle (P < 0.001), as was the mean surface area (3.5 mm2 [95 %CI 2.7 – 4.3] vs. 1.8 mm2 [95 %CI 1.2 – 2.3]; P < 0.001). Diagnostic adequacy and accuracy were 100 % and 87 % with the 22G Acquire needle, and 82 % and 67 % with the 20G Procore needle (P = 0.001 and P = 0.02, respectively).Conclusions EUS-guided biopsy of pancreatic masses with the 22G Acquire needle provided more tissue for histologic evaluation and better diagnostic accuracy than the 20G Procore needle.